Hormone‐induced repression of genes requires BRG1‐mediated H1.2 deposition at target promoters. (7th July 2016) - Nacht, Ana Silvina; Pohl, Andy; Zaurin, Roser; Soronellas, Daniel; Quilez, Javier; Sharma, Priyanka; Wright, Roni H; Beato, Miguel; Vicent, Guillermo P
Abstract: Eukaryotic gene regulation is associated with changes in chromatin compaction that modulate access to DNA regulatory sequences relevant for transcriptional activation or repression. Although much is known about the mechanism of chromatin remodeling in hormonal gene activation, how repression is accomplished is much less understood. Here we report that in breast cancer cells, ligand‐activated progesterone receptor (PR) is directly recruited to transcriptionally repressed genes involved in cell proliferation along with the kinases ERK1/2 and MSK1. PR recruits BRG1 associated with the HP1γ‐LSD1 complex repressor complex, which is further anchored via binding of HP1γ to the H3K9me3 signal deposited by SUV39H2. In contrast to what is observed during gene activation, only BRG1 and not the BAF complex is recruited to repressed promoters, likely due to local enrichment of the pioneer factor FOXA1. BRG1 participates in gene repression by interacting with H1.2, facilitating its deposition and stabilizing nucleosome positioning around the transcription start site. Our results uncover a mechanism of hormone‐dependent transcriptional repression and a novel role for BRG1 in progestin regulation of breast cancer cell growth. Synopsis: While ligand binding to progesterone receptor (PR) is known to induce transcription of target genes, the ligand‐activated PR also exerts a repressive function by recruiting BRG1 and the HP1γ‐LSD1 repressor complex. The same ternary complex of activated progesterone receptor (PR), ERK1/2, and MSK1, that mediates gene activation is also recruited to hormone‐repressed genes. The ligand‐activated PR recruits a repressor complex of HP1γ, lysine demethylase LSD1, histone deacetylases, and CoREST, also used by unliganded PR to repress target genes. The complex recruited to hormone‐repressed genes contains the ATPase BRG1 but not other members of the BAF complex. PR recruits BRG to sites marked by the pioneering factor FOXA1, leading to target chromatin remodeling via linker histone H1.2 deposition. Abstract : While ligand binding to progesterone receptor (PR) is known to induce transcription of target genes, the ligand‐activated PR also exerts a repressive function by recruiting BRG1 and the HP1γ‐LSD1 repressor complex.